On Describing the Connection between Thinking and Speaking - Jacikevičius, Aleksandras (Problemos, 1975)
A. Jacikevičius draws attention to the vague use of the terms “consciousness” and “language” in scientific literature. In the author’s view nobody has yet succeeded in developing effective experimental methods for investigating the interconnection between thinking and speech.